2018
DOI: 10.12659/msm.909290
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biological Targets of Therapeutic Intervention for Hepatocellular Carcinoma by Integrated Bioinformatical Analysis

Abstract: BackgroundWe screened the potential molecular targets and investigated the molecular mechanisms of hepatocellular carcinoma (HCC).Material/MethodsMicroarray data of GSE47786, including the 40 μM berberine-treated HepG2 human hepatoma cell line and 0.08% DMSO-treated as control cells samples, was downloaded from the GEO database. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathway (KEGG) enrichment analyses were performed; the protein–protein interaction (PPI) networks were constructed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Previous work has identified elevated EGR1 expression as a marker for drug resistance in non-TNBC (in MCF-7 cells, which are ER+) 43 ; our results indicate that EGR1 could be a therapeutic biomarker in TNBC. It has already been identified as such in other cancers (hepatocellular carcinoma and gastric cancer 44,45 ). To develop EGR1 as a relevant target in TNBC patients, we first need to better understand its role in metastasis and CSC phenotype in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work has identified elevated EGR1 expression as a marker for drug resistance in non-TNBC (in MCF-7 cells, which are ER+) 43 ; our results indicate that EGR1 could be a therapeutic biomarker in TNBC. It has already been identified as such in other cancers (hepatocellular carcinoma and gastric cancer 44,45 ). To develop EGR1 as a relevant target in TNBC patients, we first need to better understand its role in metastasis and CSC phenotype in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…The present study was the first investigation into the hepatocarcinogenesis potential mechanism using GSEA. Multiple previous studies also have identified hub DEGs between HCC tumor and non-tumor tissues, however, the hub DEGs identified by them were performed by the Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) online tool, and the database of STRING cannot represent the tissue specificity of HCC [72][73][74]. So, the hub genes identified by STRING were not real in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…C. Rhizoma was identified to target MYC using the TCMSP ( https://tcmsp-e.com/ ) ( Ru et al, 2014 ) and TCM-MESH ( http://mesh.tcm.microbioinformatics.org/ ) ( Zhang et al, 2017 ) databases, respectively ( Dong et al, 2019 ). Moreover, 56 upregulated and 8 downregulated genes of berberine-treated HCC (HepG2) cells were identified and enriched in cell cycle, cell apoptosis, and transcription ( Hu et al, 2018 ). Berberine could suppress cell proliferation and induce apoptosis by upregulating 1,960 genes and downregulating 4,837 genes, that are involved in cellular, metabolic, and single-organism processes in gastric cancer (SGC-7901) cells ( Yang et al, 2018 ).…”
Section: Omics Studiesmentioning
confidence: 99%